ANALISIS KEMAMPUAN PEMAHAMAN MATEMATIK SISWA PADA MATERI SEGIEMPAT - Aat Atikah; Euis Eti Rohaeti; M Afrilianto (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This study aims to determine the ability of mathematical understanding of class VII students on the material wake flat. The type of research used is a qualitative descriptive research. The subjects of this study consisted of 5 students selected at random. The data collected in the form of written test results as much as 5 points about the ability of students' mathematical understanding. The test results were analyzed according to the students' mathematical comprehension indicator. Data analysis is done to analyze the extent of students' mathematical understanding ability. Based on the result of research that students mathematical understanding ability still not enough in each indicator. From this research can be concluded that students mathematical understanding ability in VII grade in finished the matter of getting up flat is still low